(untitled) - Viner, Aron (Tokyo, 1988)
The emerging power of Japanese money is your guide to understanding the magnitude of Japanese domestic liquidity and its global reach. The arm of Japanese financial influence now extends from world securities markets to the most expensive office towers in New York and Los Angeles to your living room.
Keywords: Tài chính,Finance; Nhật Bản,Japan